2019
DOI: 10.1002/cche.10150
|View full text |Cite
|
Sign up to set email alerts
|

Solvent retention capacity application to assess soft wheat flour quality for making white‐salted noodles

Abstract: Background and objectives Gluten development of wheat flour under a limited amount of water is essential for dough sheeting and cutting in preparation of noodle, and for cooking and textural properties of noodles. Soft wheat flour of relatively high gluten strength, low damaged starch content, and low water absorption could be suitable for the requirement. The study was aimed at exploring the potential uses of solvent retention capacity (SRC) test for evaluation of soft wheat flour quality for making white‐sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The WSRC, LASRC, SCSRC, and SUSRC values were reported in ranges of 49.4–56.3, 90–118.5, 66–83.0, and 86.4–106.3%, respectively, for US soft wheat cultivars ( 42 ). Ram et al ( 21 ) reported WSRC values of 53.4–70.6%, LASRC of 72.0–122.8%, SCSRC of 63.9–87.2%, and SUSRC of 75.1–97.9% across 192 Indian wheat varieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WSRC, LASRC, SCSRC, and SUSRC values were reported in ranges of 49.4–56.3, 90–118.5, 66–83.0, and 86.4–106.3%, respectively, for US soft wheat cultivars ( 42 ). Ram et al ( 21 ) reported WSRC values of 53.4–70.6%, LASRC of 72.0–122.8%, SCSRC of 63.9–87.2%, and SUSRC of 75.1–97.9% across 192 Indian wheat varieties.…”
Section: Resultsmentioning
confidence: 99%
“…HD-3086 showed the highest GPI value of 0.46 and DBW-17 the lowest GPI value of 0.59. Jeon et al ( 42 ) reported GPI values of 0.52–0.69 for soft wheat cultivars. Our results are in close range with those reported.…”
Section: Resultsmentioning
confidence: 99%
“…Dried noodles with flours A and B showed similar L* (lightness), and that with flour A was slightly higher a* (redness) and b* (yellowness) than that with flour B, which indicated slightly yellowish and creamy color, whereas flour C showed much lower L* and higher a* values than did flours A and B, which revealed a much darker and reddish color due to potential higher PPO content. Jeon, Baik, and Kweon (2019) showed a significant negative correlation between PPO activity of flour and L* of raw noodles (r = −.91, p < .01).…”
Section: Characteristics Of the Dried Noodlesmentioning
confidence: 96%
“…Both protein quantity and protein quality significantly influence WSN quality (Fu, 2008; Hou et al, 2013; Park & Baik, 2009). Flour protein content and protein quality‐related parameters (lactic acid solvent retention capacity [SRC] and SDS sedimentation volume) are reported to have positive relationships with hardness of cooked WSN (Park et al, 2003; Hu et al, 2007; Hou et al, 2013; Jeon et al, 2019; Park & Baik, 2009). Starch amylose content shows a positive relationship with hardness of cooked WSN and a negative relationship with cohesiveness of cooked WSN (Baik & Lee, 2003; Guo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that selected ESW wheat varieties are suitable for making dough‐based products, such as bread (Huebner et al, 1999) and northern‐style Chinese steamed bread (Ma & Baik, 2016). More recently, Jeon et al (2019) observed that 5 out of 10 ESW wheat flours had gluten performance index (GPI) values above 0.60 and produced WSN of desirable cooking and textural properties. A limited number of studies examining comprehensive grain and flour characteristics have been conducted to identify the ESW wheat quality parameters desirable for making WSN.…”
Section: Introductionmentioning
confidence: 99%